Assessment of pedestrian access to rail transit station by spatial walkability index in Kuala Lumpur City Centre: a comprehensive approach using analytical network process and Geographical Information Science / Nurfadhilah Ruslan - Ruslan, Nurfadhilah (2023)
Walkability is one of the keys to achieve sustainable transportation in cities, as it supports a balance between environmental, social, and economic factors. Transit Oriented Development is a concept that promotes these effects. However, there are still gaps in research regarding the criteria selection and weighting methods to measure the walkability index. Additionally, there is a lack of clarity in how to define and measure walkability. This study aims to measure the Spatial Walkability Index of pedestrian access to rail transit stations in Kuala Lumpur City Centre, with three objectives: 1) to examine the set of criteria that can be used to measure walkability, 2) to determine the degree of importance of the walkability criteria, and 3) to develop the SWI for pedestrian access to rail transit stations. A set of criteria for SWI was determined through a literature review and analysis of national policies. Previous studies were reviewed to identify the most commonly used criteria to measure walkability. As a result, five (5) criteria were selected which are 1) Connectivity, 2) Land-use Mix, 3) Comfort, 4) Security, and 5) Safety, which align with national policies. Each of the criteria were represented by their ground parameters to be able to be used in geographic analysis. Then, their degree of importance of the criteria were then determined by using Analytical Network Process. The pairwise comparison method within Analytical Network Process was used to prioritize the weightage to be used as attributes in GIS software. The criterion with the highest weightage is Security (0.25), followed by Safety (0.22) which are not that different as both had always been the highest prioritized criteria in other studies too. For the ground parameters, Street Lights has the highest weightage (0.17), followed by Pedestrian Bridges (0.10). The weightage was then used in measuring Spatial Walkability Index of pedestrian access to rail transit stations by using GIS proximity analysis. This study includes both indoor and outdoor walking environment in the assessment as most of rail-transit stations in Kuala Lumpur has connection to a building, therefore people will need to walk both indoor and outdoor to access the services. As a result, the highest SWI for pedestrian access was obtained for Jalan Dato Onn near KTM Bank Negara with a value of 58.73. The highest SWI for existing rail transit stations was found at KTM Bank Negara with a value of 99.51. To ensure the model developed could be used, it was tested and validated. The inclusion of indoor walking environment was tested in KLCC LRT station where the station has direct access to the Suria KLCC.